(untitled) (Dubuque, IA, 2007)
Ever since the first EMT book was written, there have been two philosophies chosen by the authors for the reader: One type is to provide for the minimal required information and to meet only the minimum standards required by the profession. At the other end of the spectrum is the philosophy that is written to be all-inclusive. This will give the student reader (and ultimately patient care provider) the strongest knowledge possible. If you or your family were to become sick or injured in the middle of the night, in the blowing snow or in the cold rain, do you want the EMT taking care of you to be the very best they possibly could be or simply one who has taken the course to get by